1996
DOI: 10.1097/00007632-199609150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effective Doses of Recombinant Human Bone Morphogenetic Protein-2 in Experimental Spinal Fusion

Abstract: No mechanical, radiographic, or histologic differences in the quality of intertransverse process fusion resulted from a 40-fold variation in dose of recombinant human bone morphogenetic protein-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
1
7

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(91 citation statements)
references
References 19 publications
0
83
1
7
Order By: Relevance
“…To manufacture an osteoinductive artificial bone graft substitute, cytokines retaining osteoinductive activity (e.g., BMPs) have been combined with collagen and used to obtain spinal fusion in experimental animals or in human cases [1,4,5,17,25,26,35,36]. This experimental study was designed to achieve solid posterior interspinous lumbar fusion more effectively and less invasively than before with proper use of rhBMP-2 in combination with synthetic carrier materials.…”
Section: Discussionmentioning
confidence: 99%
“…To manufacture an osteoinductive artificial bone graft substitute, cytokines retaining osteoinductive activity (e.g., BMPs) have been combined with collagen and used to obtain spinal fusion in experimental animals or in human cases [1,4,5,17,25,26,35,36]. This experimental study was designed to achieve solid posterior interspinous lumbar fusion more effectively and less invasively than before with proper use of rhBMP-2 in combination with synthetic carrier materials.…”
Section: Discussionmentioning
confidence: 99%
“…number of experiments have suggested that bone morphogenetic protein (BMP) may be used to enhance bone fusion in the posterior part of the spine and perhaps even to act as a bone substitute 1,2 . In a number of recent studies, gene-therapy techniques have been used as an alternative to BMP to achieve bone formation in various animal models [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…At present, only BMP-2 and BMP-7 are produced commercially as a therapy to enhance bone healing with BMP-7 called osteogenic protein 1 (OP-1). BMP-2 and OP-1 both promote bone formation in a variety of experimental models (rat [8,13,25,46,47,56], rabbit [3,10,29,48], sheep [15,20], dog [9,19,32,35,40,43]). Although these proteins are now used clinically, most of the information on their effects is known from these and other experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, patient morbidity from graft collection in human orthopaedics is well-documented [17,40,41]. Bone graft collection in veterinary orthopaedics also is associated with patient morbidity at the donor site [45].…”
Section: Introductionmentioning
confidence: 99%